Slow magnetic relaxation in CoII–LnIII heterodinuclear complexes achieved through a functionalized nitronyl nitroxide biradical. Issue 4 (24th December 2019) - Xi, Lu; Sun, Juan; Wang, Kang; Lu, Jiao; Jing, Pei; Li, Licun
Abstract : Five nitronyl nitroxide biradical-Co II –Ln III heterodinuclear complexes were achieved and the DyCo derivative displayed visible temperature/frequency-dependent χ ′′ peaks, indicating the SMM behavior. Abstract : A new nitronyl nitroxide biradical ligand NITPh-PyPzbis (5-(3-(2-pyridinyl)-1 H -pyrazol-1-yl)-1, 3-bis(1′-oxyl-3′-oxido-4′, 4′, 5′, 5′-tetramethyl-4, 5-hydro-1 H -imidazol-2-yl)benzene) has been successfully applied for constructing a 3d–4f Co II –Ln III system, giving rise to a family of novel hetero-tri-spin complexes, namely, [LnCo(hfac)5 (NITPh-PyPzbis)]·CH2 Cl2 (LnCo = YCo 1, GdCo 2, TbCo 3, DyCo 4, and HoCo 5 ; hfac = hexafluoroacetylacetonate). In these hetero-tri-spin complexes, the NITPh-PyPzbis biradical chelates one Ln III and one Co II simultaneously by means of its adjacent aminoxyl moieties and two N donors from the 3-(2-pyridinyl)-1 H -pyrazol-1-yl unit, respectively, realizing the unique biradical-Co–Ln heterodinuclear structure. Direct-current magnetic susceptibility investigations show that antiferromagnetic coupling is predominant in the YCo derivative, while the leading magnetic interaction in the GdCo analogue is ferromagnetic. Alternating-current data for the DyCo complex display visible temperature/frequency-dependent χ ′′ peaks, indicating the SMM behavior. In the fluorescence spectra, four characteristic emission bands of the Tb III ion have been detected for the TbCo analogue.